Reliability analysis of reinforced soil walls under static and seismic forces. Issue 4 (August 2008) - Sayed, S.; Dodagoudar, G. R.; Rajagopal, K.
Abstract : The traditional factor of safety does not account for the variability and uncertainty of the different parameters considered in the analysis. On the other hand, the reliability approach considers the possible variations in the design parameters and gives more realistic estimates of the safety of the structure and the possible risk of failure. In the present investigation, reliability analysis was carried out to study the stability aspects of reinforced soil retaining walls under static and seismic conditions using three methods: first-order second-moment method (FOSM), point estimate method (PEM) and first-order reliability method (FORM). A parametric sensitivity analysis is presented to bring out the effect of uncertainties in the soil and reinforcement parameters on the value of the minimum reliability index for internal and external stability of reinforced soil walls under static and seismic loads. The reliability indices evaluated by the three methods of reliability analyses were compared for both the internal and external stability of the wall. Based on the results, it is concluded that the friction angle (ϕ) is the most sensitive random variable affecting the overall stability of the reinforced soil walls under static and seismic loads.